A Study of the Crystallization Properties of CaO-SiO2-Al2O3 Glass Phase in Sinter - Rui-Feng Xin; Xing-Min Guo (Metals, 2022)
The glass phase is one of the binding phases in high-basicity sinter, which is mainly formed during a high-temperature cooling process while cannot crystallize in time. The phase still involves the “structure” information of the binding phase’s liquid phase in the sinter. In addition, the generation of glassy phases can seriously deteriorate the metallurgical properties of sintered ore. However, the formation mechanism and crystallization process of glass phases are still unclear. In this work, the glass phase and the crystallized samples of the CaO-SiO2-Al2O3 system were characterized using X-ray diffraction, optical microscopy, scanning electron microscopy, energy-dispersive spectroscopy and Raman spectroscopy. The effect of alkalinity (R) and Al2O3 on crystallization and the relationship between crystallization and structure are discussed. The results showed that the chemical composition significantly influences the crystallization of the CaO-SiO2-Al2O3 glass. Decreasing basicity (R = 0.8–1.2, the mass ratio of CaO and SiO2) favors the crystallization of the glass phase, while increasing the content of Al2O3 (9–12%) can inhibit the crystallization of the glass phase. In addition, the crystallization order of the 45mass%CaO-45mass%SiO2-10mass%Al2O3 sample is CaSiO3 → CaAl2O4. Raman spectroscopic analysis showed that increase of slag basicity promoted the aggregation degree (Q3/Q2), resulting in deterioration of the glass phase crystallization. and that the glass phase crystallization deteriorated as the aggregation degree increased. However, increasing the Al2O3 content has little effect on the agglomeration degree but does promote the formation of SiO4 tetrahedra (Q0), which results in the deterioration of glass-phase crystallization.